Novel amylase-producing fungus hydrolyzing wheat and brewing residues, Aspergillus carbonarius, discovered in tropical forest remnant - Pasin, Thiago Machado; Dos Anjos Moreira, Eliano; de Lucas, Rosymar Coutinho; Benassi, Vivian Machado; Ziotti, Luciana Sobrani; Cereia, Mariana; Polizeli, Maria de Lourdes Teixeira de Moraes (Folia microbiologica, 2020)
Today, many microbial amylases are available commercially and they have almost completely replaced chemical hydrolysis in several industry processes. Amylases from microorganisms have a broad spectrum of industrial applications as they are more stable than amylases obtained from plants and animals. The objective of this work was to use potato baits in an Atlantic Forest remnant located in Ribeirão Preto, São Paulo, Brazil, in order to obtain amylase-producing fungi with potential for biotechnological application. In addition, the culture conditions for the fungal strain that presented higher production of glucoamylase were standardized using industrial wastes. For this, 6 PET bottles containing potatoes as baits were scattered at different points in an Atlantic forest remnant. After 6 days, the samples were collected, and the filamentous fungi were isolated in Petri dishes. Fungi screening was carried out in Khanna liquid medium with 1% starch Reagen®, at 30 °C, pH 6.0, under static conditions for 4 days. Proteins and glucoamylase activity were determined by Bradford and 3,5-dinitrosalicylic acid (DNS), respectively. Among all isolated fungi, A. carbonarius showed the highest glucoamylase production. Its best cultivation conditions were observed in Khanna medium, 4 days, at 30 °C, pH 6.0, under static condition with 0.1% yeast extract and 1% starch Reagen®. Wheat and brewing residues were also used as inducers for large quantities of glucoamylase production. A. carbonarius showed to be a good alternative for the wheat and brewing waste destinations in order to obtain high added value products.
Keywords: Brazílie; Hydrolysis; bioprospekting; glukoamylasa; tropické klima; Forests; Glucan 1,4-alpha-Glucosidase; Triticum; Aspergillus; pšenice; Tropical Climate; hydrolýza; Bioprospecting; škrob; Starch; Brazil; lesy